Necrotising Fasciitis: Clinical Evaluation and Treatment Results of 18 Patients - Anıl Murat ÖZTÜRK; Deniz AKYOL; Onur SÜER; Hüseyin Aytaç ERDEM; Ilgın YILDIRIM ŞİMŞİR; Şebnem ŞENOL AKAR; Nadir ÖZKAYIN; Meltem IŞIKGÖZ TAŞBAKAN (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Necrotizing fasciitis (NF) is a complicated and rapidly spreading soft tissue infection that affects the superficial fascia, skin, and subcutaneous tissue. In this study, we evaluated patients who were diagnosed with NF and treated in two tertiary-care educational university hospitals. Materials and Methods: Patients diagnosed with NF in three centers (Ege University Department of Orthopedics and Traumatology and Department of Infectious Diseases and Clinical Microbiology and Celal Bayar University Department of Infectious Diseases and Clinical Microbiology) between November 2016 and December 2018 were retrospectively analyzed. The patients’ demographic characteristics, significant risk factors for infection, sites of infection, models of surgical treatment, department(s) that performed the surgery, causative infectious agents, empirical and agent-specific treatment regimens and their duration, length of hospital stay, need for intensive care, and one month survival were evaluated. Results: Eighteen patients (10 females, mean age 53.7 [19-86 years]) who were diagnosed with NF were included in the study. Diabetes mellitus, trauma/surgery history, and decubitus wound were the most common predisposing factors. The most common anatomic site was lower extremity (n=10, 55.5%). All patients underwent surgical debridement. The most commonly isolated microorganisms were Escherichia coli (n=4), Klebsiella pneumoniae, Proteus mirabilis, and Acinetobacter baumannii (each n=3). Empirical treatment was initiated with meropenem in eight patients (32%) and tigecycline in four patients (12.5%), and the antibiotic was changed in five patients based on culture results. The mean duration of antibiotic therapy was 35.5 (9-68) days. The average hospital stay was 55 (11-186) days. Six patients (33.3%) required intensive care during follow-up. The mortality rate was 16.6%. Conclusion: NF is a fulminant disease, and early diagnosis and effective multidisciplinary treatment are crucial for reducing mortality rates. When the diagnosis is suspected, early surgical debridement should be performed and empirical antibiotherapy should be started immediately.